UNVEILING LINGUISTIC PATTERNS: A MORPHOLOGICAL ANALYSIS OF COMPOUND WORDS IN "THE PERKS OF BEING A WALLFLOWER" BY STEPHEN CHBOSKY - Yulianto, Andrias; Friska Rivalny, Agnechia; Angel Nayoan, Sheren; Harefa, Juvelman (La Ogi : English Language Journal, 2024)
English compound words have a significant impact on the language's structure and lexicon. This research paper focuses on conducting a morphological analysis of compound words in the novel "The Perks of Being a Wallflower" by Stephen Chbosky. The methodology includes identifying compound words in the text, analyzing their components, categorizing them based on their types, and exploring the semantic relationships between the constituent parts. A qualitative analysis was conducted to interpret the role of compound words in enhancing the narrative and conveying subtle nuances of meaning. This study identified a total of 100 compound words categorized into three types: 91 compound nouns, 4 compound verbs, and 5 compound adjectives. These compounds exhibit specific patterns of lexical categories. Specifically, there are 72 words comprising noun + noun (NN), 2 words comprising adjective + adjective (AA), 5 words comprising verb + noun (VN), 8 words comprising preposition + noun (PN), 1 word comprising preposition + verb (PV), 2 word comprising noun + adjective (NA), 7 words comprising adjective + noun (AN), and 3 words comprising noun + verb (NV). Out of these, 88 compounds have heads, while 12 compounds are headless. The analysis revealed that Chbosky effectively condenses intricate ideas into concise and impactful expressions by combining words to form compound structures and confirmed the significance of compound words in enhancing literary pieces by conveying nuanced meanings and emotional depth through the consolidation of multiple ideas into a single, evocative word that resonates with readers